2017
DOI: 10.3847/1538-4357/836/1/62
|View full text |Cite
|
Sign up to set email alerts
|

The PdBI Arcsecond Whirlpool Survey (PAWS): The Role of Spiral Arms in Cloud and Star Formation

Abstract: The process that leads to the formation of the bright star-forming sites observed along prominent spiral arms remains elusive. We present results of a multi-wavelength study of a spiral arm segment in the nearby grand-design spiral galaxy M51 that belongs to a spiral density wave and exhibits nine gas spurs. The combined observations of the (ionized, atomic, molecular, dusty) interstellar medium with star formation tracers (H II regions, young <10 Myr stellar clusters) suggest (1) no variation in giant molecul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 51 publications
8
57
1
Order By: Relevance
“…For instance, at around (4, −2)kpc and there are clear spurs pointing near-perpendicular to the arms. Such star forming spurs are seen in other disc galaxies, most noticeably in M51, where Schinnerer et al (2017) show that multiple tracers of star formation are concentrated in patches in the spurs of the arms.…”
Section: Locations Of Star Formationmentioning
confidence: 79%
“…For instance, at around (4, −2)kpc and there are clear spurs pointing near-perpendicular to the arms. Such star forming spurs are seen in other disc galaxies, most noticeably in M51, where Schinnerer et al (2017) show that multiple tracers of star formation are concentrated in patches in the spurs of the arms.…”
Section: Locations Of Star Formationmentioning
confidence: 79%
“…Keto & Myers 1986;Heyer et al 2004;Oka et al 2001;Rosolowsky & Blitz 2005;Gratier et al 2012;Wong et al 2011) also suggest common properties between GMCs in molecular-rich environments. Even the effect of the spiral potential is debated, with Schinnerer et al (2017) suggesting that the GMAs observed in M51 are actually blended gas spurs and can be separated into structures of a similar mass to inter-arm clouds. This matches simulations by Baba et al (2017) who found no evolution sequence of GMC properties across a spiral arm, although notes that the clouds are still affected by the external pressure determined by galactic-scale features.…”
Section: Introductionmentioning
confidence: 99%
“…Despite our averaging over moderately large (370 pc) areas, timescale effects may also be at play. The τ mol Dep map in Figure 9 shows significant azimuthal structure, and as shown by Schinnerer et al (2017), star formation tends to occur in spur-like structures downstream of the arms. We refer the reader to extensive discussions in Meidt et al (2013), Colombo et al (2014a), and Querejeta et al (2016), Schinnerer et al (2017), and references therein, for more discussion.…”
Section: Dynamical Statementioning
confidence: 99%
“…Galactic dynamics relate to molecular gas structure and star formation in M51 (e.g., see Koda et al 2009;Hughes et al 2013a;Colombo et al 2014a;Meidt et al 2015;Schinnerer et al 2017). With this in mind, we separate our correlation analysis by dynamical regions (Section 3.4).…”
Section: Mapping To Dynamical Regionmentioning
confidence: 99%
See 1 more Smart Citation